Molecular Interaction Studies of Galactose in Aqueous a-Amylase Solution at 298 K - Nithiyanantham, S.; Palaniappan, L. (Asian Journal of Chemistry, 2010)
The ultrasonic velocity, density and viscosity at 303 K have been measured in the ternary system of galactose with a-amylase in aqueous medium. The acoustical parameters such as adiabatic compressibility, free length, free volume and internal pressure are calculated. The results are interpreted in terms of molecular interaction between the components of the mixtures. The existence of weak interactions is confirmed by the observed excess values.